DEVELOPMENT OF CULTURE-BASED AR-ASSISTED COMICS BOOK TO ENHANCE LEARNING MOTIVATION - Mujahidawati, Mujahidawati; Sabil, Husni; Syaiful, Syaiful; Novferma, Novferma; Harizon, Harizon; Romundza, Febbry; Umam, M Afifuddin Khotibul (LPPM Universitas Jambi, 2025)
The research aims to develop, validate, and evaluate Bucomath, a culture-based mathematics comic book integrated with Augmented Reality (AR), designed to provide a contextual, interactive, and culturally relevant learning experience. Using a ADDIE model, the study involved 37 ninth-grade students and collected data through expert validation sheets, teacher and student practicality questionnaires, classroom observations, pre–post motivation scales, and structural equation modeling using SmartPLS 4. The results indicate that Bucomath achieved very high validity (83.22%) in both content and design aspects, along with strong practicality ratings from teachers and students (88.22%). The effectiveness analysis revealed a substantial improvement in learning motivation, with an N-Gain score of 0.73 categorized as high, while PLS-SEM results showed that Engagement (R² = 0.64) significantly mediated the influence of Perceived Usefulness and Perceived Enjoyment on Learning Interest (R² = 0.71), with all path coefficients statistically significant (p < 0.05). These findings suggest that the combination of cultural narratives such as Jambi traditional architecture and batik geometry with AR-based 3D visualization successfully transforms abstract mathematical concepts into concrete and emotionally engaging learning experiences. In conclusion, Bucomath demonstrates that integrating local cultural identity with immersive AR technology has strong pedagogical potential to enhance students’ intrinsic motivation, cognitive engagement, and positive attitudes toward mathematics. The implications of this study highlight that culturally responsive AR media can serve as a scalable and inclusive model for future digital learning innovations, supporting not only mathematical understanding but also cultural appreciation and identity-affirming education across diverse learning environments.